Survey data on factors that drive farmers away from straw burning in the Mekong Delta, Vietnam - Cuong, Ong Quoc; Demont, Matty; Pabuayon, Isabelita M.; Depositario, Dinah Pura T. (Elsevier BV, 2025)
The dataset presents survey data on factors that drive farmers away from straw burning in the Mekong Delta, Vietnam. Data were collected in 2019 through face-to-face interviews with 543 farmers using a structured questionnaire in four provinces: Kien Giang, An Giang, Dong Thap, and Can Tho. The dataset includes variables related to socio-economic characteristics, production factors, and geographical location that influence farmers’ choices of rice straw management practices. Further analysis and interpretive insights are available in a related research article. These data are valuable for policymakers who can use these insights to design environmental policies that discourage rice straw burning, thereby reducing environmental pollution and mitigating greenhouse gas emissions. These data can also be used in broader studies that compare the factors influencing farmers’ choices of rice straw management in developing countries.